أفكار الخوارج بين الماضي والحاضر: عرض ومناقشة - طيلون، هاني علي سليم (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنين بالقاهرة, 2019)
تعد فرقة الخوارج من أوائل الفرق الإسلامية ظهوراً في تاريخ الإسلام، بعقائدها المنحرفة، وأفكارها الشاذة، كما أنهم ليسوا حقبة تاريخية قد مضت وانتهت بآثارها السلبية المدمرة، لتدرس على أنها ظاهرة تاريخية فحسب، لا وجود لهم في الواقع، بل هم بأفكارهم وآرائهم المنحرفة الشاذة باقون متجددون عبر القرون، كلما ذهب منهم قرن نبت قرن آخر، وتظهر أهمية هذا الموضوع في كثرة ما ورد عنهم من أحاديث نبوية، بل ربما لم يرد في السنة النبوية من الأحاديث المحذرة والمبينة لفرقة من الفرق مثلما ورد في شأن الخوارج، ويرجع اختياري لهذا الموضوع من أجل خفاء حال الخوارج المتأخرين على كثير من الناس، وظهور وانتشار أفكار التكفير والتطرف والغلو في مجتمعاتنا الإسلامية، والشدة والغلظة في معاملة المسلمين مع بعضهم والتحذير لعموم المسلمين من مسالك الخوارج وطرقهم وأفكارهم. وقد اشتمل هذا البحث على التعريف بالخوارج وفرقهم وأفكارهم، من التكفير والغلو والشدة والغلظة والميل إلى الجدل، وكيفية علاج هذه الظواهر وتلك الأفكار، وبيان وسطية الإسلام، وموقفه من هذه الظواهر، ومن أهم نتائج البحث: أن الخوارج هم الذين خرجوا على الإمام علي – رضي الله عنه- بعد قبوله التحكيم في موقعة صفين، ومن وافقهم ورأى آرائهم من الناس إلى يوم الدين فهو منهم، وأن هناك عدد من الأصول والقواسم المشتركة التي اجتمع عليها عامة الخوارج من أهمها: الخروج على الإمام الجائر، ورفض التحكيم، وتكفير مرتكب الكبيرة، وأن فرقة الخوارج قد جنحت نحو الشدة والغلظة، مبتعدة عن نصوص الشرع التي تأمر بالرفق والرحمة، وأن الوسطية هي إحدى الخصائص العامة للإسلام، وإحدى المعالم الأساسية التي ميز الله- تعالى – بها أمة الإسلام عن غيرها من الأمم.
The group of the Kharijites is one of the forerunner Islamic groups that appeared in the history of Islam. This group was remarkable for its biased beliefs and strange ideas. It did not only represent a historical era that had gone away with its destructive consequences but it also represents a group that still exists in reality accompanied by its irregular beliefs and bizarre ideas which continue to appear along centuries. Whenever a century passes away a new century follows with this group at the center. The importance of this topic can be traced back to the great number of inherited Prophetic traditions which warned the Muslims against this group; namely the Kharijites. The reason why the researcher has chosen this topic is to clarify the underlying late Kharijites before the majority of people. In addition, radical, infidel and extreme ideas have spread in our Muslim societies as well as the tough and coarse treatment of the Muslims with their fellow Muslims. Moreover, the research aims at warning the publicity of Muslims against the ideas and ways of the Kharijites. The research at hand is keen to define the Kharijites, their groups and their ideas such as blasphemy, extremism, exaggeration, roughness, serenity and controversy. The research tries also to treat these phenomena and ideas as well as displaying the moderation of Islam and how these phenomena are judged in the light of its approach. Some of the most important findings of this research are stated in the conclusion. For example, the Kharijites are those who dissented from the rule of Imam Ali (May Allah be pleased with him) after his acceptance of the judgment in the battle of Seffin, and those who agree with them joined them to the Day of Judgment. The Kharijites have shared some of the basic principles such as disagreeing with the unjust ruler and refusing judgment, accusing those who commit major sins of being blasphemous. In addition, the Kharijites intended to be serene and rough though the Muslim doctrine told us to be kind and sympathetic. Moderation is one of the general characteristics of Islam and it is also one of the basic attributes that characterize the Muslims rather than any other nation.
Keywords: الفرق الإسلامية -- الخوارج -- الغلو في الدين -- التطرف الفكري -- التكفير